The effect of home-based exercise in sleep quality and excessive daytime sleepiness in elderly people: A protocol of randomized controlled clinical trial - Brandão, Glauber Sá; Callou, Antônia Adones; Brandão, Glaudson Sá; Silva, Anderson Soares; Urbano, Jessica Julioti; Junior, Newton Santos de Faria; Oliveira, Luis Vicente Franco; Camelier, Aquiles Assunção (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Sleep-disordered breathing is associated with significant morbidity and mortality, presenting a high prevalence in the general population and being considered today as an important public health problem worldwide, affecting about 45% of the world population. It is estimated that about from 50 to 75% of the elderly complain of difficulties in initiating or maintaining sleep. The regular practice of physical exercise of mild to moderate intensity is associated with improved sleep quality in the elderly and has increased its recommendation as one of the main non-pharmacological resources of preventive and therapeutic action. Objectives: To verify the effect of a semi-supervised home-based physical exercise program on sleep quality in a sedentary elderly population, which influences the improvement of self-reported sleep quality and the reduction of excessive daytime sleepiness in a sedentary elderly population. Methods: This protocol study of randomized, controlled, blinded clinical trial was designed, is being conducted and will be reported according to the guidelines of the CONSORT (Consolidated Standards of Reporting Trials) Statement, and is being conducted from July 2016 to December 2017, involving elderly people of both sexes, over 60 years old, living in Senhor do Bonfim. The home physical exercise program is based on the recommendations of the American College of Sports Medicine for exercise and physical activity for the elderly. Results: The first expected outcome is the improvement of self-reported sleep quality verified through the PSQI. The secondary outcomes are reduction in excessive daytime sleepiness among the sedentary elderly subjects undergoing the semi-supervised home-based physical exercise program, verified by the ESS, and the adherence of the subjects to the program. Conclusions: We hope that through this study, we can show that the regular practice of semi-supervised home exercises is effective in improving sleep quality and reducing excessive daytime sleepiness in sedentary elderly people and can be considered as a therapeutic, safe, easy-to-implement, and low-cost non-pharmacological resource.